2012
DOI: 10.1371/journal.pone.0030315
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genomes of Chandipura Virus Isolates and Comparative Analysis with Other Rhabdoviruses

Abstract: The Chandipura virus (CHPV) belonging to the Vesiculovirus genus and Rhabdoviridae family, has recently been associated with a number of encephalitis epidemics, with high mortality in children, in different parts of India. No full length genome sequences of CHPV isolates were available in GenBank and little is known about the molecular markers for pathogenesis. In the present study, we provide the complete genomic sequences of four isolates from epidemics during 2003–2007. These sequences along with the deduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…It is very intriguing to note that in our investigation, we observed that CHPV belonging to the VSV family is enforcing the extrinsic apoptosis pathway upon infecting the neuronal cells. The plausible reason may be that the CHPV M protein has been reported previously to have very little homology with the VSV M protein (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is very intriguing to note that in our investigation, we observed that CHPV belonging to the VSV family is enforcing the extrinsic apoptosis pathway upon infecting the neuronal cells. The plausible reason may be that the CHPV M protein has been reported previously to have very little homology with the VSV M protein (5).…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic apoptosis is mediated by the activation of cell surface death receptors belonging to the tumor necrosis factor (TNF) receptor family of proteins, including Fas/APO-1, tumor necrosis factor receptor 1, and TNF-related apoptosis-inducing ligand receptor 1 (TRAIL-R1) and TRAIL-R2 by their cognate ligands, namely, Fas ligand (FasL), TNF, and TRAIL (5,(45)(46)(47). From our qPCR array data, we observed a significant upregulation of FasL mRNA compared to that of our mock-infected control, which suggested that the apoptotic pathway after CHPV infection could be stimulated by the external death domain of FADD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspergillus flavus, sequence accession GSE32177 [79] Bacteriophage SPN3UB, sequence accession JQ288021 [80] Bamboo mitochondria, sequence accession JQ235166 to JQ235179 [81] Boea hygrometrica chloroplast, sequence accession JN107811 [82] Boea hygrometrica mitochondrial, sequence accession JN107812 [82] Canine Picornavirus, sequence accession JN831356 [83] Chandipura virus (CHPV) CIN0327, sequence accession GU212856.1 [84] Chandipura virus (CHPV) CIN0451, sequence accession GU212857.1 [84] Chandipura virus (CHPV) CIN0751, sequence accession GU212858.1 [84] Chandipura virus (CHPV) CIN0755, sequence accession GU190711.1 [84] Chinese Porcine Parvovirus Strain PPV2010, sequence accession JN872448 [85] Common midwife toad megavirus, sequence accession JQ231222 [86] Dengue Virus Serotype 4, sequence accession JN983813 [87] Duck Tembusu Virus, sequence accession JF270480 [88] Duck Tembusu Virus, sequence accession JQ314464 [88] Duck Tembusu Virus, sequence accession JQ314465 [88] Emiliania huxleyi Virus 202, sequence accession HQ634145 [89] Emiliania huxleyi Virus EhV-88, sequence accession JF974310 [89] Emiliania huxleyi EhV-201, sequence accession JF974311 [89] Emiliania huxleyi EhV-207, sequence accession JF974317 [89] Emiliania huxleyi EhV-208, sequence accession JF974318 [89] Glarea lozoyensis, sequence accession GUE00000000 [90] Nannochloropis gaditana, sequence accession AGNI00000000 [91] Oryza sativa cv., sequence accession DRA000499 [92] Partetravirus, sequence accession JN990269 [93] Porcine Bocavirus PBoV5, sequence accession JN831651 [94] Porcine epidemic diarrhea virus, sequence accession JQ282909 [95] Pseudomonas aeruginosa lytic bacteriophage PA1Ø, sequence accession HM624080 [96] Pseudomonas fluorescens phage OBP, sequence accesssion JN627160 [97] RNA Virus from Avocado, sequence accession JN880414 [98] Salmonella enterica Serovar Typhimuriu...…”
Section: Non-bacterial Genomesmentioning
confidence: 99%